[Re]moving Bodies – A Shared Diminished Reality Installation for Exploring Relational Movement - Laroche, Julien; Vuarnesson, Loup; Endaltseva, Alexandra; Dumit, Joseph; Bachrach, Asaf (Frontiers in Psychology, 2021)
In this article we explore an epistemic approach we name dis/embodiment and introduce ‘Articulations’, an interdisciplinary project bringing together Virtual Reality designers, cognitive scientists, dancers, anthropologists and human-machine interaction specialists. According to Manning (2009), our sense of Self and Other emerges from the processes of bodying and relational movement (becoming oneself by moving in relation with the world). The aim of the project is to exploit the potential of multi-person virtual reality in order to explore the intersubjective dynamics of relational movement and bodying, and to do so with scientific, artistic and therapeutic purposes in mind. To achieve this bridge, we bring up a novel paradigm we name “Shared ‘Diminished’ Reality”. It consists in using minimalist representation (as inspired by the cross-perceptual paradigm of Auvray et al., 2009) to instantiate users’ bodies in the virtual space: instead of using humanoid avatars or full body skeletons, we thus reduce the representation of the moving bodies to 3 spheres whose trajectories reflect the tracking of the head and the two wrists. This ‘diminished’ virtual rendition of the body-in-movement, we call dis/embodiment, provides a simple but clear experience of one’s own responsive movement in relation to the world and other bodies. It also allows for subtle manipulations of bodies’ perceptual and cross-perceptual feedback and simplifies the tracking and the analysis of movements. After having introduced the epistemic framework, the basic architecture, and the empirical method informing the installation, we present and discuss, as a proof-of-concept, some data collected in a situated experiment at a science-art event. We investigate motion patterns observed in different experimental conditions (in which participants either could or could not see the representation of their own hands in the virtual space) and their relation with subjective reports collected. We conclude with reflection on further possibilities of our installation in exploring bodying and relational movement.